Is the market held by institutional investors? The disposition effect revisited - Carsten Croonenbroeck; Roman Matkovskyy (European University Viadrina, Department of Business Administration and Economics, 2013)
Czarnitzki and Stadtmann (2005) measure the interdependence of demand for investment advice (approximated by sales of investor magazines) and stock prices. They find strong evidence that confirms the presence of the disposition effect, i.e. the empirical observation that investors sell winners (too) early and abide losers (too) long. We re-investigate their findings and confirm that the effect is very well present in the formerly analyzed time frame, but clearly wears off afterward. As an explanation for the decline, we provide three lines of argumentation and show that disposition effect might dependent on the shareholder structure, which is in line with the theory.
Keywords: D81; G11; G14; 330; Disposition Effect; Market Decisions; Market Efficiency; Financial Crisis; Market Structure